First direct observation of Bound-State Beta-Decay : Measurements of branching and lifetime of 207Tl81+ fragments - Boutin, David; Justus Liebig University Giessen (My University, 2005)
Der beta-Zerfall in gebundene Endzustände des freigesetzten Elektrons ist ein seit vielen Jahrzehnten vorhergesagter aber erst vor wenigen Jahren bei GSI erstmalig experimentell nachgewiesener Zerfallsprozess der schwachen Wechselwirkung. Während er in Atomen und niedrig geladenen Ionen vernachlässigbar ist, kann er die Zerfallseigenschaften in hochgeladenen Ionen und vollständig ionisierten Kernen dramatisch beeinflussen. Während diese Pionier-Experimente auf den (indirekten) Nachweis an sich bzw. auf Halbwertszeitmessungen ausgerichtet waren, waren die Ziele der vorliegenden Arbeit die erstmalige direkte Beobachtung des gebundenen beta-Zerfalls sowie die erstmalige Messung eines Verzweigungsverhältnisses des beta-Zerfalls ins Kontinuum (beta_c) und in gebundene Zustände (beta_b). Dieses Verzweigungsverhältnis, welches für die zeitumgekehrten Prozesse des Elektroneneinfangs und des beta(+)-Zerfalls theoretischund experimentell im Detail untersucht und verstanden ist, ist für den beta(-)-Zerfall bisher nur theoretisch bekannt. Für das Experiment wurde das Nuklid 207Tl ausgewählt, welches einerseits eine genügend hohe Ordnungszahl und einen hinreichend kleinen Q-Wert von etwa 1,4 MeV besitzt, so dass im Hinblick auf die Messgenauigkeit ein genügend grosses Verzweigungsverhältnis erreicht wird (die theoretische Vorhersage beträgt in diesem Fall beta_b/beta_c = 0.171(1)), andererseits ist der Q-Wert gross genug, so dass der verwendeten zeitaufgelösten Schottky-Spektroskopie benuzt werden konnte, und auch die Halbwertszeit liegt mit etwa vier Minuten in einer hinsichtlich der eingesetzten Experimentiertechnik idealen Grössenordnung. In einem Pilotexperiment wurde im Hauptexperiment erstmals die stochastische Kühlung für Sekundärstrahlen am ESR eingesetzt. Dazu wurde 207Tl durch die Fragmentationsreaktion eines 208Pb-Strahls in einem Beryllium-Target am Eingang des FRS erzeugt, mittels der Bp-DE-Bp Methode isotopenrein separiert und in den ESR eingeschossen. Durch die Kombination von stochastischer und Elektronenkühlung wurden jetzt Kühlzeiten von etwa sechs bis sieben Sekunden erzielt. Die beobachtete Halbwertszeit des 207Tl81+ liegt mit T_1/2 = 255(17) s etwa 12 % unter der des neutralen Atoms. Zwar spielen hier auch Effekte wie die fehlende Abschirmung durch die fehlende Elektronenhülle sowie die Modifikation des Q-Werts eine Rolle, der hauptsächliche Effekt aber kommt von dem nun zusätzlich verfügbaren Phasenraum, der zum neu hinzukommenden Zerfallskanal des gebundenen beta-Zerfalls führt. Das gesuchte Verzweigungsverhältnis von b/c = 0,192(20), welches in hervorragender Übereinstimmung mit dem theoretisch vorhergesagten Wert ist. Ferner kann aufgrund der kurzen Kühl- und Messzeiten auch der isomere Zustand 207mTl untersucht werden. Die Halbwertszeit des nackten isomeren Zustands gemessene Wert ist 1.47(32) s, in Übereinstimmung mit dem erwarteten Wert. Auch hierbei weicht die Halbwertszeit von der des neutralen Atoms ab 1.33(11) s, daß aufgrund der fehlenden Elektronenhülle die Möglichkeit der Konversion nicht mehr gegeben ist, was zu einer grösseren Lebensdauer führt.

It has been predicted since several decades that the change in the number of electrons bound to a particular nuclide could lead to a drastic modification of the decay properties of this nuclide. In the particular case of beta-decay, the decay 'constant' of a nuclide could be modified, due to the apparition of a 'new' decay mode, the bound-state beta-decay. It is favoured in the case of highly-ionized atoms, and can have an influence of astrophysical nucleosynthesis, in particular in the s-process. This decay mode could be observed in pioneering experiments, due to the possibility to accumulate and store highly-charged ions for a long period of time. The first experimental observation of bound-state beta-decay showed, that due solely to the electron stripping, a stable nuclide, e.g. 163Dy, became unstable. Also a drastic modification of the half-life of bare 187Re, from 4.12(2)x 10 high 10 years down to 32.9(20) years, could be observed. It was mainly due to the possibility for the mother nuclide to decay into a previously inaccessible nuclear level of the daughter nuclide. In these experiments nuclides where bound-state beta-decay was the only energetically possible decay mode have been studied. It was proposed to study a nuclide where this decay mode was competing with continuum-state beta-decay, in order to measure their respective branchings. The ratio betab/betac could also be evaluated for the first time, in contrary to the ratio EC/beta+ which had already experimental information. 207Tl was chosen due to its high atomic number, and Q-value of about 1.4 MeV, small enough to enhance the beta b probability (theoretical predictions give beta βb/beta c = 0.171(1)), and large enough to allow the use of time-resolved Schottky Mass Spectrometry (SMS) to study the evolution of mother and bound-state beta-decay daughter ions. The neutral half-life of about 5 min is ideal to study the decay of this nuclide. The decay properties of the ground state and isomeric state of 207Tl81+ have been investigated at the GSI accelerator facility in two separate experiments. These ions have been produced by the projectile fragmentation of 208Pb in a 4 g/cm2 Be target. The fragments were separated from contaminants by the in-flight fragment separator FRS. They were injected into the storage ring ESR and cooled. The electron cooling system reduced the momentum distribution of the ions down to 5x10-7. But problems with the cooling time and efficiency lead to a second experiment. This time in addition to the electron cooling the stochastic precooling was applied, for the first time for fragments. It reduced the overall cooling time down to 6-7 s. The data obtained was analyzed via time-resolved Schottky Mass Spectrometry (SMS). For the first time beta-decay where the electron could go either to a bound state (atomic orbitals) and lead to 207Pb81+ as a daughter nuclide, or to a continuum state and lead to 207Pb82+, has been observed. The respective branchings of these two processes could be measured as well. The deduced total nuclear half-life of 255(17) s for 207Tl81+, was slightly modified with respect to the half-life of the neutral atom of 286(2) s. It was nevertheless in very good agreement with calculations based on the assumption that the beta-decay was following an allowed type of transition. The branching beat b/beta c = 0.192(20), was also in very good agreement with the same calculations. The application of stochastic precooling allowed to observe in addition the 1348 keV short-lived isomeric state of 207Tl. The half-life of this isomeric state was measured as 1.47(32) s, which shows a small deviation compared to the half-life for the neutral atom, as 1.33(11) s. This difference was explained by the blocking of the internal conversion channel in the isomeric decay, due to the absence of bound electrons. From the extrapolated ratio of the 207Tl81+ particles injected into the ESR in the isomeric state to the sum of all 207Tl81+ particles injected, the isomeric production ratio of 207Tl from the fragmentation process could be evaluated as 0.15(4), which was in good agreement with calculations based on the abrasion-ablation model, deriving a value for the isomeric production ratio of 0.11.
Erste direkte Beobachtung von Gebundenem Beta-Zerfall
Keywords: Gebundene Zustände; stochastische Kühlung; Bound-state beta-decay; isomeric state; electron cooling; stochastic cooling; ddc:530